A prospective study on the role of umbilical artery doppler velocimetry in the perinatal outcome of growth restricted fetuses - R., Sumathi; Rodrigo, Mercy R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To compare pregnancy outcomes in growth-restricted fetuses retaining normal umbilical artery doppler flow and the outcomes of pregnancies with end-diastolic velocity diminished or severely reduced/absent. Methods: In a prospective observational study, one hundred pregnant women with growth-restricted fetuses were followed with doppler velocimetry of the umbilical artery between weeks 28 and 41 of pregnancy. Outcomes were compared for the normal doppler group (55%) (Group 1), the low-end diastolic flow group (32%) (Group 2), and the group with severely reduced or absent end-diastolic velocity waveforms (13%) (Group 3). Results: Fetuses with abnormal umbilical flow velocimetry had higher incidence of oligohydramnios (82.2%). The average birth weight and gestational age at delivery were lower in the abnormal doppler group. Significantly more women with severe reduction/AEDV, 31/45 (68.8%), underwent caesarean section, with 20 of them (44.4 %) for fetal distress, compared with 17/55 (30.9%) women in the normal doppler group, with 9 of them (16.4%) for fetal distress. Also, fetuses with abnormal umbilical artery velocimetry had early delivery at less than 36 weeks of gestation (38.2% versus 65.85%), increased NICU admission (32.7% versus 80%), need for PPV (5.5% versus 40%), low Apgar score (9.1 % versus 50.2%) than those with normal doppler. All the three stillbirths in the study population were in the abnormal doppler group. Conclusions: Umbilical artery doppler velocimetry helps in differentiating fetus with pathological growth restriction at risk for perinatal complications from small and healthy fetuses.